A Comparative Study of the Proton Properties of Magnetospheric Substorms at Earth and Mercury in the Near Magnetotail. Issue 16 (17th August 2018) - Sun, W. J.; Slavin, J. A.; Dewey, R. M.; Raines, J. M.; Fu, S. Y.; Wei, Y.; Karlsson, T.; Poh, G. K.; Jia, X.; Gershman, D. J.; Zong, Q. G.; Wan, W. X.; et al.
Abstract: The variations of plasma sheet proton properties during magnetospheric substorms at Earth and Mercury are comparatively studied. This study utilizes kappa distributions to interpret proton properties at both planets. Proton number densities are found to be around an order of magnitude higher, temperatures several times smaller, and κ values broader at Mercury than at Earth. Protons become denser and cooler during the growth phase, and are depleted and heated after the dipolarizations in both magnetospheres. The changes of κ at Earth are generally small (<20%), indicating that spectrum‐preserving processes, like adiabatic betatron acceleration, play an important role there, while variations of κ at Mercury are large (>60%), indicating the importance of spectrum‐altering processes there, such as acceleration due to nonadiabatic cross‐tail particle motions and wave‐particle interactions. This comparative study reveals important intrinsic properties on the energization of protons in both magnetospheres. Plain Language Summary: Earth and Mercury are the only two planets possessing global intrinsic magnetic fields among the four inner planets, which are Mercury, Venus, Earth, and Mars, within the solar system. The interactions between the intrinsic magnetic fields and the continual flow of high‐speed solar wind from the Sun form similar magnetospheres at the two planets, although the scale of the magnetosphere is much smaller at Mercury than at Earth. Magnetospheric substorms, a result of solar wind–magnetosphere coupling, occur in both magnetospheres. Comparative study of a similar process between different planets is meaningful as it can help us in understanding the specific process further as well as help us in understanding the intrinsic properties of the magnetospheres. This research paper characterizes the proton properties of magnetospheric substorms of both planets, revealing that different mechanisms control the behavior of protons during the magnetospheric substorms of the two planets. Key Points: Proton number densities are an order of magnitude higher, temperatures several times smaller, and κ values broader at Mercury than at Earth Protons become denser and cooler during the growth phase, and are depleted and heated after the substorm dipolarizations at both planets κ changes are <20% at Earth, implying spectrum‐preserving accelerations, and >60% at Mercury, implying spectrum‐altering accelerations